1969
DOI: 10.1063/1.1657643
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Alnico Alloy Phases and Temperature Instability of Permanent Magnets

Abstract: Analysis of the structural constituents of Alnico alloys with high coercive force showed that the saturation magnetization of the α′ phase is quite high, and for Alnico VIII and Alnico VS55 is close to the saturation of binary Fe–Co (Is∼1800 emu) At the same time, the saturation magnetization of the α phase is only several scores of emu. The relative volume of α′-phase decreases from Alnico V to Alnico VIII and VS55. This result is in qualitative agreement with the corresponding decrease of Is and increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Using advanced characterization and simulation tools [11][12][13][14][15][16][17][18][19], in particular aberrationcorrected scanning transmission electron microscopy (STEM) and in-situ Lorentz microscopy, we describe the crucial microstructure and magnetization features of a commercial alnico 9 that give rise to the highest energy product of ~10.5MGOe in the alnico family. Armed with this information, key processing and chemical modifications are proposed for further improving the energy product of alnico [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Using advanced characterization and simulation tools [11][12][13][14][15][16][17][18][19], in particular aberrationcorrected scanning transmission electron microscopy (STEM) and in-situ Lorentz microscopy, we describe the crucial microstructure and magnetization features of a commercial alnico 9 that give rise to the highest energy product of ~10.5MGOe in the alnico family. Armed with this information, key processing and chemical modifications are proposed for further improving the energy product of alnico [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, permanent magnets are divided into two groups, rare earth-free magnets and rare earth-containing ones. The group of rare earthfree magnets consists of Alnico, Ferrite, etc [2][3][4][5][6][7], which contain cheap components but their quality is not high. In contrast, the rare earth magnets such as Nd-Fe-B [8] and Sm-Co [9,10] have good quality but high cost, due to content of rare earth elements, which are concentrated in only a few countries and restricted to exploitation as well as exportation.…”
Section: Introductionmentioning
confidence: 99%
“…Alnico alloys achieve their best magnetic properties after a complicated heat-treatment (HT) process, which includes a high temperature (∼1250 • C) solution treatment, followed by short-time thermal-magnetic annealing (∼800 • C) and a long-time lower temperature stepped drawing (∼550-700 • C) [8]. Previous studies indicated that the magnetic properties of alnico are sensitive to the time and temperature of the magnetic field annealing (MA), as well as to the constituent elements of the alloy, including minor additions [4,[8][9][10][11][12][13][14][15]. However, a comprehensive investigation on how different HT parameters affect the microstructure and magnetic property evolution of alnico is lacking.…”
Section: Introductionmentioning
confidence: 99%